Representation of Standard Language on The Dilan Characters in The Novel "Dilan 1990" - Cahyani Dara; Marudut Bernadtua Simanjuntak (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Dilan is 1990’s novel by Pidi Baiq. The novel, which was published by Pastel Books in 2014, was able to achieve maximum sales, especially in terms of youth segmentation. This can be seen from the high enthusiasm of young people toward Dilan's novels. It is not surprising that the novel can attract readers, judging by the interesting and simple story ideas as well as the humorous and romantic demeanor. In addition, the storyline of the characters in it can be told very well by the author accompanied by dialogue, and the words in it are written using standard language characters and accents. Thus, this writing is structured based on the aim of presenting the use of standard language for the character Dilan in the novel Dilan: Dia is Dilanku in 1990. The writing method used to support this writing is using a qualitative method.